2010
DOI: 10.7150/ijms.7.248
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic glioma: Report of one case and review of the literature

Abstract: We report one case of brain glioma that developed in the scar of an old brain trauma. A 45-year-old man who presented with seizures; MRI showed a large mass in the right temporal region. Surgical biopsy showed a glioblastoma multiforme. The patient had suffered a cranial trauma in a road accident 10 years previously with an intracerebral hematoma in the right temporal region. This case fulfills the established criteria for a traumatic origin of brain tumors and adds further support to the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 6 publications
1
38
0
Order By: Relevance
“…In a Danish cohort study, that included patients hospitalized for concussion, fractured skull or any other head trauma, the incidence of gliomas was the same as for the general population (131). Several authors reported cases that indicated head trauma as the cause of gliomas and its influence needs to be further investigated (132).…”
Section: Head Traumamentioning
confidence: 99%
“…In a Danish cohort study, that included patients hospitalized for concussion, fractured skull or any other head trauma, the incidence of gliomas was the same as for the general population (131). Several authors reported cases that indicated head trauma as the cause of gliomas and its influence needs to be further investigated (132).…”
Section: Head Traumamentioning
confidence: 99%
“…For a long time, head injury has been considered as a possible causative factor for later development of brain tumors [1]. However, the actual role of previous head trauma in the pathogenesis of intracranial tumors is still a matter of debate [1], also due to the possible medico-legal implications [2].…”
Section: Introductionmentioning
confidence: 99%
“…With the routine use of CT and MRI, some of the pathologic criteria can be replaced or supplemented by imaging criteria. CT/MRI, which elegantly reveal the severity and location of the traumatic brain injury and the subsequent formation of a neoplasm at the same site, can provide convincing evidence for the traumatic causation of a brain tumor [6].…”
Section: Discussionmentioning
confidence: 99%